Therapeutic accessibility of caspase-mediated cell death as a key pathomechanism in indirect acute lung injury - Perl, Mario; Chung, Chun-Shiang; Perl, Ulrike; Thakkar, Rajan; Lomas-Neira, Joanne; Ayala, Alfred (Critical care medicine, 2010)
Indirect acute lung injury is associated with high morbidity and mortality. However, the underlying pathophysiology is only marginally understood, and so far no pathophysiologic-based remedy exists. We hypothesized that apoptosis of lung epithelial cells is a pathophysiological relevant process in the development of indirect acute lung injury and that it should be accessible to a siRNA-based therapeutic intervention in vivo. Prospective, randomized, controlled animal study. Basic science laboratory of a university affiliated level one trauma center. Male C3H/HeN mice, 8 wks old, n = 121. First, siRNA sequences to knock-down caspase-3 expression at a RNA and protein level were evaluated in vitro. Then, C3H/HeN mice were subjected to hemorrhagic shock, after which they received either a caspase-3 siRNA or a control/nonsense siRNA. Subsequently, they were then subjected to polymicrobial sepsis (induced by cecal ligation and puncture). Twelve and 24 hrs after sepsis, increased lung epithelial apoptosis was observed, as evidenced by active caspase-3 Western blotting, caspase-3, TUNEL-, and M-30 immunohistochemistry. Hallmarks of acute lung injury, such as increased concentrations of pulmonary cytokines/chemokines, lung protein leakage, myeloperoxidase activity, and altered lung histology, were evident in response to these insults. The single intratracheal instillation of caspase-3 siRNA not only attenuated lung apoptosis and inflammation but also ameliorated the development of acute lung injury in treated mice. Most interestingly, this experimental therapeutic approach markedly improved 10-day survival of hemorrhaged septic mice. Apoptosis of lung epithelial cells is a relevant pathomechanism in the development of hemorrhage-induced indirect septic acute lung injury, and caspase-3 appears to be a valuable therapeutic target accessible by siRNA treatment in vivo.